2007
DOI: 10.1177/03946320070200s205
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Symptoms of Medical Students Exposed to Formaldehyde during a Gross Anatomy Dissection Course

Abstract: The purpose of this study is to investigate the safety of and to try to find the best plan to cope with exposure to FA for students during a gross anatomy dissection course. The FA exposure level and subjective symptoms was estimated. The relationship between exposure to FA and subjective symptoms of irritation were discussed for times; before, in the beginning period, in the middle period, and upon completion of the Anatomy Dissection Course. The geometric means of FA concentration were 32.7 micrograms/m3 (be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…(11) Wei et al observed that symptoms due to formalin exposure are dependent on time spent in dissection hall and suggested to reducing time spent while dissection could reduce symptoms. (12) Since formaldehyde is toxic, search for alternative and safer fixative was done. Frolich et al in 1984 discovered nontoxic phenoxyethanol, but it took approximately 600 litres for fixing a cadaver and continuous immersion for 5-10 months was required thus eliminating its practical use.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Wei et al observed that symptoms due to formalin exposure are dependent on time spent in dissection hall and suggested to reducing time spent while dissection could reduce symptoms. (12) Since formaldehyde is toxic, search for alternative and safer fixative was done. Frolich et al in 1984 discovered nontoxic phenoxyethanol, but it took approximately 600 litres for fixing a cadaver and continuous immersion for 5-10 months was required thus eliminating its practical use.…”
Section: Discussionmentioning
confidence: 99%
“…; Wei et al. ; Khaliq & Tripathi, ; Lakchayapakorn & Watchalayarn, ; Ahmed, ; Mirabelli et al. ; Vohra, ; Raja & Sultana, ).…”
Section: Preservatives or Fixativesunclassified
“…Wei CN et al observed that manifestations because of formalin presentation were subject to time spent in dissection hall and proposed that lessening time spent while dissection could reduce symptoms. [16] Finding an alternative for formalin is likewise a decent choice to avert unsafe impacts of formaldehyde. Glutaraldehyde would be a reasonable option with similar fixation qualities.…”
Section: Discussionmentioning
confidence: 99%